Farmers' retirement pension : how social aspects and information collection affect farmers' retirement planning - Johansson, Caroline (SLU/Dept. of Economics, 2016)
The retirement scheme is not easy to understand and it is hard to know how the rules should be applied at an individual basis. It is at the same time essential to have a financial security as future pensioner. People being employed have a favorable security giving them both national retirement- and occupational pension, in general automatically. The issue prevails when it comes to planning retirement pension for self-employees, who often are in need of stability. This is the case for family businesses, where a firm's financial position is closely related to that of the owner. The approximately 500,000 self-employees in Sweden today endure a difficult situation facing a complex retirement pension. Thereby the present study focuses on Swedish farmers' decision-making and their retirement planning, including how and why they act in a certain way. This thesis uses four key aspects to keep a distinct structure. The key aspects are information collection, knowledge, social aspects, and farmers' decision-making. The aim of this study is to explore how farmers handle information and how social aspects influence the early stages in their decision-making regarding retirement pension. This knowledge makes it possible to clarify patterns that may exist among farmers' retirement decisions. It is desirable to get data that is quantifiable and therefore a quantitative approach was suitable. To reach the aim a web-based questionnaire was sent by e-mail to 3,000 members of The Federation of Swedish Farmers (LRF). A statistical test, named chi-square test, is used to explore patterns among farmers' retirement planning. The chi-square test measures the degree of linkage between two variables. The risk of calculation being random is 10% with a p-value of 0,10 as the limit to determine whether the hypothesis should be accepted or rejected. The results reveal the most evident correlation between loan-to-value ratio (acronym LTV) and retirement saving. Farmers with a low LTV tend to save less money in other forms (such as equity funds, national retirement-, occupational pension and pension insurance) than those with a higher LTV. The results also show a correlation between how much rented land of total cultivated land farmers use and their tendency to save to retirement pension in other forms than the real estate. The most likely reason behind these correlations is that the invested value in agricultural properties is the farmers retirement saving. The findings also show an unmistakable correlation between the farmers' interest in business matters and their knowledge about retirement saving. Furthermore the more knowledge that claim to have, to more willing are they to search for more information within the topic. The conclusion of the study is that individuals' interest correlate with their knowledge, which makes them more likely to search for more information. An interest is therefore of great importance on how actively the individual plans how to save for retirement. The complexity within the Sedish retirement pension scheme makes people more active in their decision making. Yet another obvious conclusion of this survey is that very few farmers are talking about retirement-related issues with family and friends. Neither the previous generation nor the successor have any influence on how active decision-making regarding retirement savings the individual have. Still, the existence of a successor affects when the farmer will reitre.